Better Late Than Never - A Case of a Congenital Left Partial Anomalous Pulmonary Venous Drainage Diagnosed and Treated in The Sixth Decade of Life - Elbayomi, Mohamed; Pathare, Presheet; Nooh, Ehab; Harig, Frank; Abdullayev, Farid; Weyand, Michael (Heart Surgery Forum, 2023)
Partial anomalous pulmonary venous drainage (PAPVD) is a relatively uncommon cardiac anomaly. The diagnosis might be challenging as are the presenting symptoms. Its clinical course mimics more familiar diseases, e.g., pulmonary artery embolism. We present a case of PAPVD, which had been misdiagnosed for more than two decades. After establishing the correct diagnosis, the patient got his congenital anomaly surgically corrected and showed excellent cardiac recovery in the six months follow up.
CRIS-Team Scopus Importer:2023-04-07

Double valve replacement in a case of Hedinger syndrome - Pathare, Presheet; Weyand, Michael; Heim, Christian (Clinical Case Reports, 2023)
Hedinger Syndrome or carcinoid heart disease is a rare cardiac complication of neuroendocrine tumors (NET) affecting the tricuspid and pulmonary valves. Following is a case description of a patient undergoing treatment for a neuroendocrine tumor with liver metastasis, referred with symptomatic tricuspid valve regurgitation and pulmonary valve stenosis for surgical valve replacement. Planned surgical valve replacement was successfully performed before the onset of severe right ventricular failure or pulmonary hypertension in this case of carcinoid heart disease. An interdisciplinary approach and regular follow up is recommended in such cases.
CRIS-Team WoS Importer:2023-02-03

MELD-score for risk stratification in cardiac surgery - Pathare, Presheet; Elbayomi, Mohamed; Weyand, Michael; Griesbach, Colin; Harig, Frank (Heart and Vessels, 2023)
The outcome of the patients undergoing cardiac surgery with cardiopulmonary bypass (CPB) is also influenced by the renal and hepatic organ functions. Risk stratification, using scores such as EURO Score II or STS Short-Term Risk Calculator for patients undergoing cardiac surgery with cardiopulmonary bypass, ignores the quantitative renal and hepatic function; therefore, MELD-Score was applied in these cases. We retrospectively examined patient data using the MELD score as a predictor of mortality. To perform a univariate analysis of the data, patients were classified into three groups based on the MELD Score: MELD < 10 (Group 1), MELD 10 to 19 (Group 2), and MELD ≥ 20 (Group 3). A total of 11,477 participants were included in the study, though several patients with either missing MELD scores or lack of creatinine, bilirubin, or INR levels were dropped from the original cohort. Eventually, 10,882 patients were included in the analysis. The primary outcome was defined as postoperative, in-hospital mortality. Secondary outcomes such as postoperative bleeding, including the requirement for repeat thoracotomy, postoperative neurological complications, and assessment of catecholamines on weaning from cardiopulmonary bypass/ requirement of mechanical circulatory support were examined. A higher MELD score was associated with increased postoperative mortality. Patients with MELD > 20 experienced a 31.2% postoperative mortality, compared to Group 1 (4.6%) and Group 2 (17.5%). The highest rates of postoperative bleeding (13.8%) and, repeat thoracotomy (13.2%) & postoperative pneumonia (17.4%) were seen in Group 3 (threefold increase when compared to Group 1, renal failure requiring dialysis (N = 235, 2.7% in Group 1 v/s N = 78, 22.9% in Group 3) or requiring high dose catecholamines post-operatively or mechanical circulatory support (IABP/ECLS). Incidentally, an increased MELD Score was not associated with a significant increase in the postoperative incidence of stroke/TIA or the presence of sternal wound infections/complications. A higher mortality was observed in patients with reduced liver and renal function, with a significant increase in patients with a MELD score > 20. As the current risk stratification scores do not consider this, we recommend applying the MELD score before considering patients for cardiac surgery.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Cardiac surgery; Liver disease; MELD; Preoperative

Prolapsing Left Atrial Mass Presenting as Syncope - Pathare, Presheet; Weyand, Michael; Heim, Christian (Thoracic and Cardiovascular Surgeon Reports, 2022)
Background Myxomas are the most common primary cardiac tumor in adults and are most commonly found within the left atrium. These are usually asymptomatic, detected incidentally, or present gradually with symptoms typical of heart failure.
CRIS-Team WoS Importer:2022-07-29

Single-Center Retrospective Analysis of Acute Type A Aortic Dissection Outcome and Reoperation Focusing on Extended Versus Limited Initial Repair - Elbayomi, Mohamed; Weyand, Michael; Pathare, Presheet; Nooh, Ehab; Harig, Frank (Heart Surgery Forum, 2023)
Background: The optimal management strategy for acute aortic type A dissection remains controversial. Whether a limited primary (index) repair would increase the need for late aortic reintervention is still an open debate.Methods: A total of 393 consecutive adult patients with acute type A aortic dissection who underwent cardiac surgery were analyzed. Our research hypothesis was whether limited aortic index repair (i.e., isolated aorta ascending replace-ment without an open distal anastomosis with and without a concomitant aortic valve replacement, including hemiarch replacement procedure) is associated with a higher incidence of late aortic reoperation compared with extended repair (i.e., any other surgical procedure that goes beyond that limited approach).Results: Type of the initial repair had no statically sig-nificant relationship with in-hospital mortality with a P-value of 0.12, however in multivariable analysis, cross-clamp time had a statistically significant relation with mortality (P = 0.4). From the patients who survived until discharge (N = 311), 40 patients needed a reoperation on the aorta; the mean interval until reoperation was 4.5 years. The relationship between the type of the initial repair and the need for reoperation didn't reach a statically significant value (P = 0.9). In-hospitable mortality after the second operation was 10% (N = 4).Conclusion: We reached two conclusions. 1) An extended prophylactic repair in the initial operation of an acute type A aortic dissection might not lead to a lower incidence of reoperations on the aorta and could increase in-hospital mor-tality by increasing cross-clamp time, and 2) Reoperation on the aorta could be done safely with acceptable mortality outcomes.
CRIS-Team WoS Importer:2023-03-31

Successive surgical repair of a progressive aortic dissection in a case of Loeys–Dietz Syndrome - Pathare, Presheet; Elbayomi, Mohamed; Tandler, Rene; Weyand, Michael; Harig, Frank (Journal of Cardiac Surgery, 2022)
Introduction: The Frozen Elephant Trunk technique is a well-established treatment for aortic dissections (Stanford Type A) involving the aortic arch and descending aorta. The Thoraflex™ Hybrid prosthesis (Vascutek Ltd.), consisting of a proximal flexible conduit and a distal self-expanding covered stent, has consistently shown positive results in the treatment of this condition. Case Description: The following is a description of such a staged reconstruction using the Thoraflex™ Hybrid Ante-Flo™ device, performed in a patient previously diagnosed with Loeys–Dietz Syndrome. After clamping the aorta proximally, an incision was taken at the distal end of the stent. Here, the distal end of the new prosthesis was inserted into the true lumen of the descending aorta and the stent was deployed. Following this, a bypass was established via the left atrium, and blood was returned to the lower body using the perfusion arm of the prosthesis with the proximal part of the descending aorta clamped. The collar of the prosthesis was sutured proximally to the aorta near the inlying previous stent. Air was removed via the perfusion arm of the prosthesis, which was then oversewn. Discussion: To date, hybrid prostheses have only been used on the proximal aorta in patients with aortic aneurysms and aortic dissections (Stanford Type A). Conclusion: Using the described technique, it is possible to reconstruct the aortic anatomy using the available prostheses with accuracy and minimal complications.
CRIS-Team Scopus Importer:2022-12-02
Keywords: aorta and great vessels; perfusion

The mystery of methylene blue and its role in managing post-cardiac surgery vasoplegic shock - Elbayomi, Mohamed; Dewald, Oliver; Pathare, Presheet; Kondruweit, Markus; Tandler, Rene; Weyand, Michael; Heim, Christian (Annals of Medicine, 2025)
Background: Vasoplegic syndrome is associated with high mortality. Methylene blue (MB) is a guanylate cyclase inhibitor that ameliorates this re-distributive type of shock. This study aims to investigate the outcome in patients who received MB early postoperatively. Methods: 2753 patients who underwent cardiac surgery utilizing cardiopulmonary bypass at our institution in a time interval of two years were identified. The incidence of vasoplegic syndrome was 7.2% (n = 200). Pharmacy records identified 84 patients (group 1, MB group) who received methylene blue and 116 patients (group 2, Control group) who didn’t receive the drug. This single-center retrospective cohort study’s primary outcome was in-hospital mortality. Secondary outcomes were postoperative hemodialysis, serum lactate levels at 24 h postoperatively, and intensive care unit stay length in days. Results: MB patients have a shorter ICU stay as compared to the control group (9 ± 8 days vs. 16 ± 6.9; p-value <.001). In the control group, postoperative hemodialysis was higher (20% in the MB group and 40% in the control group; p-value <.05). At 24 h post-op, the methylene blue group had reduced serum lactate levels (1.8 ± 1.2 vs. 4 ± 1.8 in the control group; p-value <.001). The methylene blue group had a decreased 24-hour norepinephrine dose (1.5 ± 1.2 vs. 2.8 ± 2 in the control group; p-value <.05). In-hospital mortality was not significantly different between the two groups (38% in the MB group vs. 43% in the control group). Conclusion: Early postoperative administration of methylene blue in patients with vasoplegic syndrome shortens intensive care unit stay and contributes to less end-organ damage.
CRIS-Team Scopus Importer:2025-02-14
Keywords: Cardiopulmonary bypass; methylene blue; vasoplegic syndrome